Sense-making approach in determining information seeking and usage : case study in health communication / Ismail Sualman and Rosni Jaafar - Sualman, Ismail; Jaafar, Rosni (Universiti Teknologi MARA, Shah Alam, 2011)
Communication research view communication as a process of transferring information from the source to the receiver to influence an individual's behavior. The focus of past research have been on the transmission of information involving the media and not on the relevancy of information needed by individuals. The aim of this research is to study communication as information seeking efforts. Therefore, one of the objectives of the research is to look at factors influencing the needs and usage of health communication among the public. The research utilizes the sense-making approach as its theoretical framework. In general, the research indicates significant relationships between situational factors and efforts toward fulfilling information needs and information seeking. The research findings differ from the traditional communication research approaches which mostly focus on the effect of information on individuals. This research strongly indicates that individuals who face a health situation will actively seek relevant information to overcome their health predicaments.